Monitoring swine virus transmission in embryos derived from commercial abattoir oocytes - Pepin, Brent; Rodriguez-Villamil, Paula; Sammel, Lauren; Yin, Jie; Dacken, Brian (Frontiers in Veterinary Science, 2024)
Pigs are pivotal in agriculture and biomedical research and hold promise for xenotransplantation. Specific-pathogen-free (SPF) herds are essential for commercial swine production and xenotransplantation research facilities. Commercial herds aim to safeguard animal health, welfare, and productivity, and research facilities require SPF status to protect immunocompromised patients. Somatic cell nuclear transfer (SCNT) embryos are the norm for producing cloned and genetically edited animals. Oocytes for embryo reconstruction are most conveniently sourced from commercial abattoirs with unclear disease statuses. However, research on viral clearance from donor oocytes during embryo reconstruction remains limited. SCNT has previously been shown to reduce the transmission of Porcine reproductive and respiratory syndrome virus, Bovine viral diarrhea virus, Porcine Circovirus type 2, and Porcine parvovirus. Still, it is lacking for other pathogens, including endogenous viruses. This project contains two preliminary studies investigating the polymerase chain reaction (PCR) assay detection of common swine viruses through the phases of producing parthenogenic and SCNT embryos. Exogenous pathogens detected in oocyte donor tissue or the oocyte maturation media were not detected in the produced embryos. Porcine endogenous retrovirus type C (PERVC) was not removed by parthenogenic embryo activation and was detected in 1 of the 2 tested SCNT embryos reconstructed using a PERVC-negative cell line. SCNT and parthenogenic embryo construction similarly reduced exogenous virus detection. SCNT embryo construction helped reduce endogenous virus detection. This project demonstrates the importance of screening embryos for endogenous viruses and shows the usefulness of parthenogenic embryos in future exogenous virus clearance studies.